2019
DOI: 10.1007/s41030-019-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Burden of Illness in a Prevalent COPD Population Treated with Long-Acting Muscarinic Antagonist Monotherapy: A Claims-Linked Patient Survey Study

Abstract: Introduction: Symptom burden in inadequately controlled chronic obstructive pulmonary disease (COPD) considerably impacts quality of life, healthcare resource utilization (HCRU) and associated costs. This claims-linked cross-sectional survey study assessed symptom burden and HCRU among a prevalent population of COPD patients prescribed long-acting muscarinic antagonist (LAMA) monotherapy. Methods: Patients were identified using claims data from the Optum Research Database. Eligible patients were aged C 40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…The CAT has been found to be a reliable, appropriate, and responsive instrument for measuring symptom burden in patients with COPD [6,10,24,26,27], and has demonstrated good correlation with established QoL questionnaires, including the SGRQ, and other relevant measures of disease severity [28,29]. This is consistent with published data, where a high level of correlation between measures of COPD symptom burden was noted, with [ 70% of patients obtaining high scores on at least two PROs (Supplementary Table 1) [11].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The CAT has been found to be a reliable, appropriate, and responsive instrument for measuring symptom burden in patients with COPD [6,10,24,26,27], and has demonstrated good correlation with established QoL questionnaires, including the SGRQ, and other relevant measures of disease severity [28,29]. This is consistent with published data, where a high level of correlation between measures of COPD symptom burden was noted, with [ 70% of patients obtaining high scores on at least two PROs (Supplementary Table 1) [11].…”
Section: Discussionsupporting
confidence: 83%
“…The study was a multivariable analysis of a previously reported claims-linked, cross-sectional survey of patients with COPD who were enrolled in commercial or Medicare Advantage (MA) insurance plans and prescribed LAMA monotherapy (study 205862 [HO-16-16642]) [11]. Medical and pharmacy claims and enrollment data from the Optum Research Database (ORD) were used to identify patients between October 1, 2015 and September 30, 2016.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations